2014
DOI: 10.1186/bf03353058
|View full text |Cite|
|
Sign up to set email alerts
|

Ground motion and rupture process of the 2003 Tokachi-oki earthquake obtained from strong motion data of K-NET and KiK-net

Abstract: A great earthquake, named the 2003 Tokachi-oki earthquake, occurred in the southern Kuril subduction zone on 26th September 2003, 4:50 JST (41.7797 • N, 144.0795• E, 42 km depth; Japan Meteorological Agency). Its ground motion was recoreded at 655 stations of the nationwide strong motion networks, K-NET and KiK-net. A maximum peak ground acceleration of 988 cm/s 2 (gal) was observed at station HKD100 and amplitudes greater than 200 cm/s 2 were observed over a wide area of eastern Hokkaido. We used a multi-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 18 publications
6
86
0
Order By: Relevance
“…[14] We also found significant slip in the northeast area of the fault plane, as inferred by Yamanaka and Kikuchi [2003] and Honda et al [2004] but not by Yagi [2004]. Koketsu et al [2004] show a smooth broad slip distribution centered near our highest slip but lacking any clear slip locus in the northeast region of the fault.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…[14] We also found significant slip in the northeast area of the fault plane, as inferred by Yamanaka and Kikuchi [2003] and Honda et al [2004] but not by Yagi [2004]. Koketsu et al [2004] show a smooth broad slip distribution centered near our highest slip but lacking any clear slip locus in the northeast region of the fault.…”
Section: Resultssupporting
confidence: 55%
“…The larger slip patch is located where neither significant afterslip nor aftershocks [Ito et al, 2004] were observed; the region of smaller slip is located at the deeper edge of the afterslip. On the other hand, seismic waveform inversion studies [Honda et al, 2004;Yagi, 2004] find a maximum downdip where more than 20 cm of afterslip was observed. We suggest that almost all of the accumulated stress was released by highspeed rupture in ''asperities'' [Yamanaka and Kikuchi, 2004], and that afterslip and some aftershocks were concentrated in the surrounding regions due to stress transfer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations